Legal Analysis of Land Redistribution Policy and Protection of The Rights of Indigenous Communities Syria-Ria Province of North Sumatra - Stefany Oktaviana; Rita Alfiana (International Journal of Science and Environment (IJSE), 2026)
Inequality in land ownership remains a pressing agrarian issue in Indonesia, particularly for indigenous communities whose territories frequently clash with state claims. Land redistribution policies, as part of the agrarian reform agenda, are intended to achieve justice and equal access to land. However, their implementation often faces structural obstacles, particularly in areas with customary rights. This study analyzes the implementation of land redistribution policies and the protection of the rights of the Siria-Ria indigenous community in North Sumatra Province through a normative juridical approach referring to laws and regulations, doctrines, and empirical data. The study findings indicate that the implementation of land redistribution in Siria-Ria Village still does not provide legal certainty due to disharmony between Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA) and Law Number 41 of 1999 concerning Forestry (Forestry Law), resulting in overlapping authority between the ATR/BPN and the Ministry of Environment and Forestry. The determination of forest areas through Decree of the Minister of Forestry No. 579/Menhut-II/2014 and the establishment of the food estate program through Decree of the Minister of Environment and Forestry No. 448/2020 and Presidential Decree No. 131 of 2024 have reduced the living space of indigenous peoples and ignored the principle of protecting customary rights as guaranteed in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia (UUD 1945), Constitutional Court Decision No. 35/PUU-X/2012, and the principle of free, prior, and informed consent (FPIC). Thus, the state needs to harmonize regulations, formally determine customary areas, and implement stronger legal protection so that land redistribution policies can truly realize agrarian justice for the indigenous people of Syria-Ria.